1999
DOI: 10.1007/s11745-999-0441-1
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis and apoptotic mediators in balb/C splenic lymphocytes by dietary n−3 and n−6 fatty acids

Abstract: The present study was designed to investigate the effect of dietary n-6 and n-3 polyunsaturated fatty acids (PUFA) on anti-CD3 and anti-Fas antibody-induced apoptosis and its mediators in mouse spleen cells. Nutritionally adequate semipurified diets containing either 5% w/w corn oil (n-6 PUFA) or fish oil (n-3 PUFA) were fed to weanling female Balb/C mice, and 24 wk later mice were sacrificed. In n-3 PUFA-fed mice, serum and splenocyte lipid peroxides were increased by 20 and 28.3% respectively, compared to n-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 70 publications
4
22
0
2
Order By: Relevance
“…Moreover, increased apoptosis was observed also in normal splenic lymphocytes obtained from Balb/c mice treated with a fish oil diet [158]. Either a decrease of Bcl-2 and an increase of FAS-ligand was observed in the lymphocytes, confirming in this case the possible induction of both the intrinsic and extrinsic apoptotic pathways by n-3 PUFAs.…”
Section: Other Cancer Cellsmentioning
confidence: 52%
“…Moreover, increased apoptosis was observed also in normal splenic lymphocytes obtained from Balb/c mice treated with a fish oil diet [158]. Either a decrease of Bcl-2 and an increase of FAS-ligand was observed in the lymphocytes, confirming in this case the possible induction of both the intrinsic and extrinsic apoptotic pathways by n-3 PUFAs.…”
Section: Other Cancer Cellsmentioning
confidence: 52%
“…In particular, it was shown that DHA was able to alter the expression and the activity of caspase-8 and -9 in colon cancer and HL-60 lymphoma cells [59,60]. Moreover, EPA induced an increased activity of caspase-3 and -9 in the lymphoma Ramos cell line [59] and dietary n-3 PUFAs were able to decrease BCL-2 and increase FAS-ligand expression in normal splenic lymphocytes of Balb/c mice [61]. Alteration of BCL-2 family proteins, cytochrome c release and mitochondrial membrane depolarization were induced by EPA and DHA in colon cancer cells [3,62,63].…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have clearly demonstrated that the content of long-chain PUFA n-3 fatty acids and/or the ratio of n-6/n-3 fatty acids in the diet modulates many measures of Tcell function. These include the ability to proliferate in response to mitogen/antigen stimulation and to mount a delayed-type hypersensitivity response (68)(69)(70)(71)(72)(73). The physiological interpretation of how T-cell function is altered by these lipids is far from clear.…”
Section: Pufa and T-cell Function (Adult And Animals)mentioning
confidence: 99%